Active Control of Resonant Cloaking in a Terahertz MEMS Metamaterial. Issue 16 (31st May 2018) - Manjappa, Manukumara; Pitchappa, Prakash; Wang, Nan; Lee, Chengkuo; Singh, Ranjan
Abstract: Metamaterials exhibiting exotic optical properties have played a significant role over the years in guiding the concept of invisibility cloaking from the realm of being fiction to reality. However, due to the difficulties in fabricating the 3D cloaking devices and lack of exotic plasmonic materials at terahertz (THz) frequencies, the experimental realization of cloaking phenomenon in the THz spectrum is challenging. In this work, a new mechanism for invisibility cloaking based on the resonant scattering cancellation technique in a 2D nonconcentric composite metamaterial device, consisting of a split ring resonator (SRR) and a microelectromechanical system (MEMS) reconfigurable closed ring resonator (CRR) at THz frequencies is reported. A strong magnetic interaction between the SRR and CRR eliminates the scattering effects from the SRR at its fundamental eigen mode frequency, thereby making it invisible to the incident THz wave. Further, by voltage actuation of MEMS‐reconfigurable CRR, an active switching between the visible and cloaked states of SRR structure is demonstrated. The proposed technique provides a simple design and technique for realizing invisibility cloaks by utilizing the resonant near‐field interactions in the subwavelength structures across microwave to optical frequencies, thereby circumventing the need for materials with complex geometry and exotic properties. Abstract : Metamaterials have played a prominent role in realizing invisibility cloaks operating across a wide band of the electromagnetic spectrum. Here, a coupling‐induced resonant cloaking of the split ring resonator (SRR) meta‐atom at terahertz frequencies is experimentally demonstrated. Additionally, active switching between visible and cloaked states of the SRR using voltage actuation of a MEMS‐reconfigurable closed ring resonator (CRR) meta‐atom is demonstrated.